(untitled) (Research, Society and Development, 2022)
Objective: Electronic identification as available from the patient’s medical record (PEP) technological solution in the context of Dentistry. Methodology: The present work corresponds to a narrative literature review, which aimed to review current literature available in the following databases: Lilacs (Latin American and Caribbean Literature in Health Sciences), PubMed and SciELO (Scientific Electronic Library Online), which addressed the topic of choice, using pre-established descriptors, including articles from the last 05 years, available in full, and excluding those that were only distant from the proposed topic. Results: After applying the selected inclusion and exclusion criteria, 18 articles and 2 resolutions from the Federal Dentistry Council were selected to integrate the study, for the choice of quality of findings for the challenges of the main findings of the implementation of the PEP. Conclusion: PEP was identified as a tool that enables information security, privacy and longevity.